The myth of "Africans did it to themselves": Resistance as the Norm - Nsiangani, Kibavuidi (CEMA - USK, 2021)
This paper argues that African resistance, not “African complicity,” is the baseline pattern in the history of Atlantic deportations and their afterlives. Using the Kingdom of Kongo as a primary case, it shows that systematic violence, racial dehumanisation and explicit contempt for Africans were present from the start of European expansion. These conditions made equal “trade” and shared ideology impossible. Collaboration by African elites therefore has to be read as a survival strategy and a profile formed under power imbalance, not as proof of innate anti-self racism. I combine four strands of evidence. First, Afonso I’s letters, Kongo oral traditions and archaeological studies reveal a kingdom that experienced and resisted depopulation, and that remembered Mpanzu a Nzinga as a kind, legitimate ruler overthrown in what can be read as the first Western-backed coup in Kongo memory. Second, demographic reconstruction from Paper 1 shows several million people removed or killed from the broader Kongo catchment, far beyond the 1.8 million documented in surviving Portuguese records, which must be treated as a censored minimum. Third, psychological theories of the Dark Tetrad, moral disengagement and dehumanisation, applied at institutional scale, help explain why European actors turned domination into a moral entitlement and why they cultivated co-opted elites. Fourth, comparative cases from other African kingdoms, apartheid South Africa and non-African contexts illustrate that similar patterns of structural violence, elite capture and scapegoating appear wherever one group strips another of basic humanity. We differentiate servitude and captive incorporation in African and other societies from racialised chattel slavery and systematic invasion. They differ in scope, in effects and in philosophical and psychological foundations. The paper integrates these threads into a simple principle. Resistance is the norm where human beings face organised dehumanisation. Collaborators and their profiles are products of asymmetrical power and deliberate engineering. Treating them as proof that “Africans did it to themselves” is only possible once Africans have already been stripped of full humanity in the eyes of the observer.